Vida y muerte de una espada atlántica del Bronce Final en Europa: Reconstrucción de los procesos de fabricación, uso y destrucción - Quilliec, Bénédicte T. (Complutum, 2007)
The cutting of all archeological artefacts no given systematic or even impossible in number cases, macro- and microscopic observations whitout sample are extremely important. They give us many informations about technical processes allowed to made metallic objects. With traces interpretations about metalic objects using surface exames we can propose initial stages and explain cause of these stigmates or how they were made. In this article I will present different interpretations of the traces observed on Atlantic swords from the Late Bronze Age (c. 1350-800 BC).